2005
DOI: 10.1103/physrevb.72.224435
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance and magnetic characterization of theGd5.09Ge2.03Si1.88

Abstract: Electron spin resonance was applied on samples of Gd 5.09 Ge 2.03 Si 1.88 . The results are discussed under the scope of magnetization measurements, optical metallography, and wavelength dispersive spectroscopy. Polycrystalline arc-melted samples submitted to different heat treatments were investigated. The correlation of the electron spin resonance and magnetization results permitted a characterization of the present phases and their transitions. Two coexisting phases in the temperature range between two phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The weak temperature dependence of H res and the Dysonian line shape indicate a typical paramagneticlike behavior. 13 Corroborating the above results with thermal and magnetization studies, the observed H res in the high temperature regime corresponds to paramagnetic austenite ͑PA͒ phase.…”
Section: Resultssupporting
confidence: 62%
“…The weak temperature dependence of H res and the Dysonian line shape indicate a typical paramagneticlike behavior. 13 Corroborating the above results with thermal and magnetization studies, the observed H res in the high temperature regime corresponds to paramagnetic austenite ͑PA͒ phase.…”
Section: Resultssupporting
confidence: 62%
“…A second-order magnetic transition appears around 300 K, and in this transition the MCE is negligible when compared to the MCE calculated for the first-order transition [4]. When the T c is close to room temperature, the material becomes a good candidate for application in domestic magnetic refrigeration systems.…”
Section: Introductionmentioning
confidence: 88%
“…The samples were characterized by magnetic analysis and the results have shown an intense first-order transition (typical for the Gd 5 Ge 2 Si 2 monoclinic phase) at 266 K and a small second-order transition (typical for the Gd 5 Si 4 orthorhombic phase) at 300 K for the as-cast bulk samples [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is common, however, the formation of other phases than the one with the nominal stoichiometry, with phase transitions occurring in temperatures relatively close to each other. Usually one of the transitions is of first order type and the other is of second order type [3]. …”
Section: Methodsmentioning
confidence: 99%